Preoperative concerns of patients undergoing endoscopic sinus surgery. Issue 8 (9th April 2014) - Yeung, Jeffrey C.; Brandt, Michael G.; Franklin, Jason H.; Doyle, Philip C.; Rotenberg, Brian W.; Kilty, Shaun J.
<x xml:space="preserve">Abstract</x> Background Patient‐centered care is recognized as being fundamental to successful medical practice. The effectiveness of patient‐centered care has classically been measured by posttreatment outcomes, such as patient compliance and psychosocial responses. Systematic assessment of patient concerns prior to treatment has been limited, to date. Endoscopic sinus surgery (ESS) is an elective procedure for chronic rhinosinusitis that carries a clear, defined set of risks. The objective of this prospective observational study was to determine the concerns of patients undergoing ESS for chronic rhinosinusitis. Methods A total of 180 patients undergoing ESS for chronic rhinosinusitis with or without polyposis were recruited at 2 Canadian tertiary care centers. They completed a validated survey assessing their concerns regarding the risks and outcomes of surgery. Data was analyzed using descriptive statistics and analysis of variance. Results Patients had a low degree of concern prior to undergoing surgery (overall score 2.8/9), though individual variability existed. Subjects felt the greatest level of concern regarding potential need for revision surgery as well as the wait time for surgery. Patients were least concerned about psychological factors (mean = 1.8/9). No differences with respect to age or gender were identified. Mean scores for cerebrospinal fluid leak and orbital injury were 3 and 3.2, respectively. Conclusion Patients' level of concern prior to undergoing elective surgery is generally low. Patients' areas of greatest concern may not align with those perceived by the physician. This study provides insight into patient concerns prior to undergoing elective sinus surgery and emphasizes the importance of the patient‐centered approach to care.